2005
DOI: 10.1111/j.1365-2958.2005.04534.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Type III secretion substrate specificity switch (T3S4) domain in YscP from Yersinia enterocolitica

Abstract: SummaryThe length of the needle ending the Yersinia Ysc injectisome is determined by YscP, a protein acting as a molecular ruler. In addition, YscP is required for Yop secretion. In the present paper, by a systematic deletion analysis, we localized accurately the region required for Yop secretion between residues 405 and 500. As this C-terminal region of YscP has also been shown to control needle length it probably represents the substrate specificity switch of the machinery. By a bioinformatics analysis, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
106
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 55 publications
3
106
1
Order By: Relevance
“…HrpP has a C-terminal T3S4 like that of the Yersinia YscP, but HrpP and its homologs in other plant pathogens are much smaller (1). This observation suggests that HrpP has a role in substrate switching but is not a molecular ruler controlling pilus length in P. syringae.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…HrpP has a C-terminal T3S4 like that of the Yersinia YscP, but HrpP and its homologs in other plant pathogens are much smaller (1). This observation suggests that HrpP has a role in substrate switching but is not a molecular ruler controlling pilus length in P. syringae.…”
mentioning
confidence: 71%
“…The Yersinia YscP protein functions as a molecular ruler that determines the length of the YscF needle (31). The YscP protein also has a type III secretion substrate specificity switch domain (T3S4), which acts in concert with YscU to switch pathway traffic from channel components to effectors (1). The length of YscP controls the length of the needle so that the needle can extend beyond bacterial surface structures (notably the YadA adhesin), thus enabling needle contact with the host cell cytoplasmic membrane (39).…”
mentioning
confidence: 99%
“…However, as bacteria encounter immune cells during infection, type III secretion becomes essential in preventing phagocytic killing of the invading microbes (50,65,66). The expression of genes encoding type III machines and their substrates is regulated in all bacterial species, and there is increasing evidence not only that each microbial species employs unique sets of genes encoding type III effector proteins for host cell injection but also that the order in which these polypeptides are transported is developmentally determined (1,32,39,59).…”
mentioning
confidence: 99%
“…To date, the molecular mechanisms underlying the T3S substrate specificity switch have been studied intensively in animal-pathogenic bacteria. It has been shown that the switch depends on secreted regulatory proteins, designated T3S substrate specificity switch (T3S4) proteins and including, e.g., YscP from Yersinia spp., Spa32 from Shigella flexneri, and FliK from the flagellar T3S system (1,35,50,53,66). T3S4 proteins share limited amino acid sequence similarity with each other but contain a structurally conserved C-terminal domain, termed the T3S4 domain, which is presumably crucial for protein function (1,9,52,56).…”
mentioning
confidence: 99%
“…It has been shown that the switch depends on secreted regulatory proteins, designated T3S substrate specificity switch (T3S4) proteins and including, e.g., YscP from Yersinia spp., Spa32 from Shigella flexneri, and FliK from the flagellar T3S system (1,35,50,53,66). T3S4 proteins share limited amino acid sequence similarity with each other but contain a structurally conserved C-terminal domain, termed the T3S4 domain, which is presumably crucial for protein function (1,9,52,56). Experimental evidence reported for Spa32 and FliK suggests that T3S4 proteins interact with the C-terminal cytoplasmic domains of members of the conserved FlhB/YscU family of inner membrane proteins, which are proposed to be involved in the recognition of T3S substrates (9,54,55).…”
mentioning
confidence: 99%